1997
DOI: 10.1006/dbio.1996.8486
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Zbu1, a DNA-Binding Member of the SWI2/SNF2 Family

Abstract: The SWI2/SNF2 gene family has been implicated in a wide variety of processes, involving regulation of DNA structure and chromatin configuration, mitotic chromosome segregation, and DNA repair. Here we report the characterization of the Zbu1 gene, also known as HIP116, located on human chromosome band 3q25, which encodes a DNA-binding member of this superfamily. Zbu1 was isolated in this study by its affinity for a site in the myosin light chain 1/3 enhancer. The protein has single-stranded DNA-dependent ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 39 publications
4
58
0
2
Order By: Relevance
“…For example, HLTF activates the PA 1-1 promoter via specific binding to a promoter element (16), and in other studies, HLTF has been shown to bind to the simian virus 40 (SV40) enhancer, the myosin light chain locus enhancer, and HIV long terminal repeats (17)(18)(19)(20). Interestingly, humans have at least two different forms of HLTF protein that differ in their translation initiation site, and it is the shorter form that lacks the Ϸ120 N-terminal residues that exhibit the sequencespecific DNA binding activity and is transcriptionally active (16).…”
Section: Discussionmentioning
confidence: 93%
“…For example, HLTF activates the PA 1-1 promoter via specific binding to a promoter element (16), and in other studies, HLTF has been shown to bind to the simian virus 40 (SV40) enhancer, the myosin light chain locus enhancer, and HIV long terminal repeats (17)(18)(19)(20). Interestingly, humans have at least two different forms of HLTF protein that differ in their translation initiation site, and it is the shorter form that lacks the Ϸ120 N-terminal residues that exhibit the sequencespecific DNA binding activity and is transcriptionally active (16).…”
Section: Discussionmentioning
confidence: 93%
“…This resulted in detection of 22 genes whose expression was associated with the degree of histologic differentiation. It is noteworthy that, of these proteins, 13 (DAD1, 45 plakoglobin, 46 catenin ␣, 47 insulin-like growth factor binding protein 2, 48 core binding factor, 49 Smad4/DPC4, 50 nuclear factor I/x, 51 Cip1-interacting zinc finger protein, 52 HIP116 SNF2/SW12-related transcriptional factor, 53 cyclin G2, 54 E2F3, 55 replication factor c, 56 and disheveled 3 57 ) were transcriptional factors or tissue-specific expression proteins related to cell differentiation or development. Moreover, of these genes, core binding factor, 58 Smad4/ DPC4, 50 Cip1-interacting zinc finger protein, 52 E2F3, 55 replication factor c, 59 and disheveled 3 57 were reportedly related to p21.…”
Section: Discussionmentioning
confidence: 99%
“…Membership in the SWI͞SNF superfamily is defined by a structure of seven DNAdependent ATPase motifs that is conserved in organisms from yeast to humans, and as members of multiprotein complexes SWI͞SNF proteins use the energy of ATP hydrolysis to alter nucleosome position or spacing (4,5). In addition to chromatin reorganization, SWI͞SNF-related proteins have been implicated in many aspects of cellular function, including maintenance of chromosome stability and proper chromosome segregation (lodestar) (6), recombination (RAD54 and RAD54b), nucleotide excision repair (RAD4, ERCC6, and RAD16) (7), and transcriptional activation or repression (MOT1 and HLTF) (8)(9)(10)(11). Although most SWI͞SNF proteins lack specific DNAbinding motifs and are thought to contribute to transcriptional activation by perturbing chromatin structure to allow promoter access for sequence-specific activator proteins, select members of the SWI͞SNF family, such as CHD1 and HLTF (helicase-like transcription factor, also called HIP116a, Zbu1, RUSH1a, and Smarca3) have sequence-specific DNA-binding domains and so can be targeted to specific promoters directly (9,12,13).…”
mentioning
confidence: 99%